2018
DOI: 10.3844/jcssp.2018.1599.1610
|View full text |Cite
|
Sign up to set email alerts
|

Huffman Based Code Generation Algorithms: Data Compression Perspectives

Abstract: This article proposes two dynamic Huffman based code generation algorithms, namely Octanary and Hexanary algorithm, for data compression. Faster encoding and decoding process is very important in data compression area. We propose tribit-based (Octanary) and quadbitbased (Hexanary) algorithm and compare the performance with the existing widely used single bit (Binary) and recently introduced dibit (Quaternary) algorithms. The decoding algorithms for the proposed techniques have also been described. After assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In 2018, Habib et al [7] published a paper on tribit (octernary tree) and quadbit (hexadecimal tree) Huffman encoding and compared it with previously proposed dualbit (quaternary tree) and the Zopfli algorithm [8]. They did not coincide with our experimentation results.…”
Section: Introductionmentioning
confidence: 54%
“…In 2018, Habib et al [7] published a paper on tribit (octernary tree) and quadbit (hexadecimal tree) Huffman encoding and compared it with previously proposed dualbit (quaternary tree) and the Zopfli algorithm [8]. They did not coincide with our experimentation results.…”
Section: Introductionmentioning
confidence: 54%
“…This research has analysed the performance of algorithms that have been made with Huffman-based techniques in terms of decoding speed and compression ratio. This study shows that the proposed decoding algorithm outperforms the Huffman-based technique in terms of speed while compression performance remains almost the same [3].…”
Section: Figure 1 Huffman Algorithm Flowchartmentioning
confidence: 72%
“…After assessing all the results, it was found that the Octonary and the Hexanary technique performed better than the existing techniques in terms of encoding and decoding speed. Use MPLS-TE for multimedia applications [3].…”
Section: Figure 1 Huffman Algorithm Flowchartmentioning
confidence: 99%
“…As we know, the traditional Huffman can construct a binary tree based on the frequency of the symbols shown in Figure 4, but the tree is not balanced [21], [28] though. Meanwhile, consider the first sample text for the transliterated English from Table II.…”
Section: B Decoding Time Complexity For Regular Huffmanmentioning
confidence: 99%
“…It can generate an optimum codeword so the tree can follow the 2-bit process that helps to perform the decoding on O(log 4 n) in the opposite of O(log 2 n) for traditional binary Huffman. Habib et al, [21] further upgraded their research and proposed Octanary (tribitbased) and Hexanary (quadbit-based) approaches that outperform both encoding and decoding time for some existing methods Zopfli and quaternary.…”
mentioning
confidence: 99%